Insightful acetone gas sensing behaviour of Ce substituted MgFe2O4 spinel nano-ferrites - Prince S. Mkwae; Ioannis Kortidis; Robin E. Kroon; Nompumelelo Leshabane; Mudalo Jozela; Hendrik C. Swart; Steven S. Nkosi (Journal of Materials Research and Technology, 2020)
MgCexFe2-xO4 (0 ≤ x ≤ 0.2) nanoparticles have been produced by the glyco-thermal technique and characterized by X-ray diffraction, electron microscopy, X-ray photoelectron spectroscopy, Mössbauer spectroscopy and gas sensing analyses. The X-ray diffraction results indicated that a pure cubic spinel phase was formed for samples having a low concentration of Ce, but the high Ce doping (x = 0.2) of magnesium ferrite resulted in the formation of secondary phases. The crystallite size of the compounds ranged from 2.2 nm to 15.3 nm. The 57Fe Mössbauer spectra showed transformation from an ordered to a paramagnetic spin state with an increase in Ce concentration. Gas sensors fabricated from the spinel ferrites were tested towards various organic compound vapours (acetone, methanol, p-xylene, ethylbenzene, toluene, and benzene) at an operating temperature of 225 °C. The MgCe0.2Fe1.8O4 nanoferrite proved to possess quality sensor characteristics of high sensitivity and selectivity to acetone vapour, with a response of over 500@100 ppm concentration as well as reproducibility, reversibility, and stability of over 120 days. This sensor not only displayed high responses, but could also maintain them over 1, 3, 5, 10, 20, and 30 min of acetone exposure time. The sensor was resilient and sensitive to an oxygen reduced, inert ambient environment. Under relative humidity, the response was reduced, but stable, due to physisorbed water molecules.